Effect of Absorber plate material on flat plate collector efficiency - Sup, Billy (2010)
The study was conducted to investigate the effect of absorber plate material on the efficiency of heat-absorbing flat plate collectors. Aluminum and copper used in this study because of the heat transfer ability of both materials is high. Absorber plate thicknesses used were 1 millimeter and 2 millimeters which is suitable for the conduction of heat to the working fluid. A model was designed for the experiment. The model was horizontal to the ground during the experiment which conducted from 1000H to 1700H. Inlet and outlet temperature were tabulated into a table with a fix fluid flow rate. Based on the results of the study, 2 millimeters thick aluminum absorber of heat is suitable for use in solar energy collectors. This indicates that aluminum absorber plate is a better absorber of heat in the context of this study. Aluminum is capable of absorbing heat and store heat longer than copper and contributes to high efficiency of the flat plate collector.